Self-Selection of Frequency Tables with Bilateral Mismatches in an Acoustic Simulation of a Cochlear Implant - Fitzgerald, Matthew B. (J Am Acad Audiol, 2017)
BACKGROUND: Many recipients of bilateral cochlear implants (CIs) may have differences in electrode insertion depth. Previous reports indicate that when a bilateral mismatch is imposed, performance on tests of speech understanding or sound localization becomes worse. If recipients of bilateral CIs cannot adjust to a difference in insertion depth, adjustments to the frequency table may be necessary to maximize bilateral performance. PURPOSE: The purpose of this study was to examine the feasibility of using real-time manipulations of the frequency table to offset any decrements in performance resulting from a bilateral mismatch. RESEARCH DESIGN: A simulation of a CI was used because it allows for explicit control of the size of a bilateral mismatch. Such control is not available with users of CIs. STUDY SAMPLE: A total of 31 normal-hearing young adults participated in this study. DATA COLLECTION AND ANALYSIS: Using a CI simulation, four bilateral mismatch conditions (0, 0.75, 1.5, and 3 mm) were created. In the left ear, the analysis filters and noise bands of the CI simulation were the same. In the right ear, the noise bands were shifted higher in frequency to simulate a bilateral mismatch. Then, listeners selected a frequency table in the right ear that was perceived as maximizing bilateral speech intelligibility. Word-recognition scores were then assessed for each bilateral mismatch condition. Listeners were tested with both a standard frequency table, which preserved a bilateral mismatch, or with their self-selected frequency table. RESULTS: Consistent with previous reports, bilateral mismatches of 1.5 and 3 mm yielded decrements in word recognition when the standard table was used in both ears. However, when listeners used the self-selected frequency table, performance was the same regardless of the size of the bilateral mismatch. CONCLUSIONS: Self-selection of a frequency table appears to be a feasible method for ameliorating the negative effects of a bilateral mismatch. These data may have implications for recipients of bilateral CIs who cannot adapt to a bilateral mismatch, because they suggest that (1) such individuals may benefit from modification of the frequency table in one ear and (2) self-selection of a “most intelligible” frequency table may be a useful tool for determining how the frequency table should be altered to optimize speech recognition.